Fetal sex and risk of preeclampsia: Dose maternal race matter?. (2nd September 2022) - Mirzakhani, Hooman; Weiss, Scott T.
Abstract: Objective: To examine whether maternal race could affect the relationship between fetal sex and preeclampsia. Material and methods: This study was a cohort analysis using prospectively collected data from pregnant women who participated in the Vitamin Antenatal Asthma Reduction Trial (VDAART). Preeclampsia was the secondary outcome of VDAART. We examined the association of fetal sex with preeclampsia and its potential interaction with maternal race in 813 pregnant women (8% with preeclampsia) in logistic regression models with adjustment for preterm birth (<37 weeks of gestation), maternal age, education, and body mass index at enrollment and clinical center. We further conducted a race stratified analysis and also examined whether any observed association was dependent on the gestational age at delivery and prematurity. Results: In an analysis of all races combined, preeclampsia was not more common among pregnant women with a male fetus compared to those with a female fetus (odds ratio [OR] = 1.3, 95% CI = 0.81, 2.24). There was an interaction between African American race and fetal sex in association with preeclampsia after adjustment for preterm delivery and other potential confounders ( p  = .014). In race stratified analyses, we observed higher odds of preeclampsia among African American pregnant women who carried male fetuses after adjustment for preterm delivery and other potential confounders (adjusted OR = 2.4, 95% CI = 1.12, 5.60). Conclusion: We observed fetal sexual dimorphic differences in the occurrence of preeclampsia in African American women, but not in Whites. Information on fetal sex may ultimately improve the prediction of pre-eclampsia in African American mothers, who might be at higher risk for this adverse condition in pregnancy.